2021
DOI: 10.1016/j.xinn.2021.100083
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Heating Induced by Tadpole-like Downflows in the Flaring Solar Corona

Abstract: Tadpole-like flows known as supra-arcade downflows are observed in a solar flare.-Many such flows are found to collide with the flare arcade.-The collisions cause strong heating of the local plasma to a temperature of 10-20 MK.-These heating events generate quasi-periodic pulsations (QPPs) in solar radiation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 46 publications
4
15
0
1
Order By: Relevance
“…However, orbital period modulation might still be inferred when such an FRB source is in our galaxy or a very nearby galaxy so that an X-ray or even optical counterpart could be detected. 36 , 37 The donor could be either a white dwarf or a low-mass star since the general trend in the stability of hydrogen-poor accretion disks is similar to that of a hydrogen disk. 35 If we assume that different-frequency emissions of FRBs are produced at different altitudes within the pulsar magnetosphere, 19 the observed chromatic activity window could be explained by the drift of the main collapse regions during the high accretion state.…”
Section: Resultsmentioning
confidence: 99%
“…However, orbital period modulation might still be inferred when such an FRB source is in our galaxy or a very nearby galaxy so that an X-ray or even optical counterpart could be detected. 36 , 37 The donor could be either a white dwarf or a low-mass star since the general trend in the stability of hydrogen-poor accretion disks is similar to that of a hydrogen disk. 35 If we assume that different-frequency emissions of FRBs are produced at different altitudes within the pulsar magnetosphere, 19 the observed chromatic activity window could be explained by the drift of the main collapse regions during the high accretion state.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, observations of such phenomena have been reported in the literature [60,61]. However, these may only represent localized events in the interface region where the overall downwardcontracting magnetic loops dominate the plasma motion.…”
Section: Methodsmentioning
confidence: 94%
“…Some of the works are focused on the magnetic energy injection from the photosphere into the upper atmosphere, which can shed light on the coronal heating problem. 79 Mackay et al. 26 modeled the decaying phase of AR NOAA 8005 using SOHO/MDI magnetograms, quantified the free energy accumulation as driven by the magnetic flux dispersal, and concluded that the injected free energy is sufficient to explain the radiative losses at coronal temperatures within the AR.…”
Section: Data-driven Modeling Of the Slow Evolution Of Coronal Magnet...mentioning
confidence: 99%